Discovery and redescription of type material of Nausithoe simplex (Kirkpatrick, 1890), comb. nov. (Cnidaria: Scyphozoa: Coronatae: Nausithoidae) from the North Atlantic - Morandini, André C.; Jarms, Gerhard (Zootaxa, 2012)
With discovery and examination of type specimens in the Natural History Museum, London, UK, we reassign Stephanoscyph-istoma simplex (Kirkpatrick, 1890) to the genus Nausithoe Kölliker, 1853, as Nausithoe simplex, comb. nov., and designate alectotype for the species. Use of morphometric measurements is considered important in coronate systematics, but key featuresalso include the unique whorl of internal cusps and the shape of these cusps. All previous records of N. simplex must be re-evaluated, taking into consideration the morphology of these internal cusps.